Experimental and Numerical Simulation Studies of RC Beams under the Actions of Equal Energy Impact Loads - Xiwu Zhou; Xiangyu Wang; Runcheng Zhang; Wen Zhang (Advances in Civil Engineering)
In this study, two groups of RC beams were subjected to low-speed drop weight impact test by using the domestic advanced ultrahigh heavy-duty drop weight impact testing machine system. The main aspects studied are the influence of the combination of different impact velocity and mass on the dynamic response and local and global damage change of RC beam under the same impact energy. Next, the numerical model considering material strain rate is established using ABAQUS finite element software to verify and expand the experimental results. The results show the following: (1) under the condition of equal energy, the peak value of impact force measured in this experiment increases with the increase of impact velocity, yet the mid span displacement and rebar strain first increase and then decrease. In addition, when the impact velocity is 2.25 m/s and the impact mass is 400 kg, the beam has the most serious damage; (2) compared with the mass, the impact velocity has more obvious effects on the peak value of cumulative impact force, mid span displacement, and rebar strain; (3) with the decrease of the impact velocity (the increase of the mass), the local damage of the beam is gradually weakened and the overall damage is gradually exacerbated. The failure mode of the beam is transformed from local punching shear failure to overall static failure type.